Micropropagation of Anthurium adreanum from leaf explants - ATAK, ÇİMEN; ÇELİK, ÖZGE (Department of Molecular Biology and Genetics, Faculty of Science and Letters, Istanbul Kultur University, Ataköy, Istanbul, Turkey, 2009)
Anthurium propagation by tissue culture techniques appears as an alternative to increase the production. Plant regeneration of Anthurium andraeanum cultivars “Arizona” and “Sumi” (Anthura) has been achieved through adventitious shoots formation from callus. The leaf explants were used for the propagation by indirect organogenesis. Callus induction medium consisted of half-strength MS basal salt with 0.6 mg/l 2,4-D, 1 mg/l BA. Shoot regeneration medium consisted of modified halfstrength MS salts with NH4NO3 lowered to 250 mg/l, 0.1 mg/l 2, 4-D and 1 mg/l BA. Rooting medium was (modified half-strength MS salts) supplemented with 1mg/l IBA and 0.04%active charcoals. The callus induction rate of Arizona variety was higher as compared to Sumi variety and this increase was found significant. The number of shoots per explants for Arizona variety also significantly increased as compared to Sumi variety. Arizona and Sumi root percentages were high and these percentages were 98% and 95% respectively. The results showed that Arizona variety had different responses as compared to Sumi variety for callus induction and the number of shoots per explants. Shoot multiplication for two varieties increased in the multiplication stages and this increase in number of shoots per explants were found important (p<0.05).
Keywords: Anthurium; micropropagation; tissue culture